Influences of Neo-Pleistocene permafrost on thermal history of petromaternal Lower Jurassic Togur suite (Tomsk region); IOP Conference Series: Earth and Environmental Science; Vol. 43 : Problems of Geology and Subsurface Development - Iskorkina A. A. Albina Albertovna (Mineralogy, Geochemistry and Petrography, 2016)
Title screen